OsNAC2 Is Involved in Multiple Hormonal Pathways to Mediate Germination of Rice Seeds and Establishment of Seedling - Yu, Jiangtao; Mao, Chanjuan; Zhong, Qun; Yao, Xuefeng; Li, Peng; Liu, Chunming; Ming, Feng (Frontiers in Plant Science, 2021)
The germination of seeds and establishment of seedling are the preconditions of plant growth and are antagonistically regulated by multiple phytohormones, e.g., ethylene, abscisic acid (ABA), and gibberellic acid (GA). However, the interactions between these phytohormones and their upstream transcriptional regulation during the seed and seedling growth in rice remain poorly understood. Here, we demonstrated a rice NAC (NAM-ATAF-CUC) transcription factor, OsNAC2, the overexpression of which increases the ethylene sensitivity in rice roots during the seedling period. Further study proved that OsNAC2 directly activates the expressions of OsACO and OsACO3, enhancing ethylene synthesis, and then retards seedling establishment. Moreover, OsNAC2 delays the germination of seeds and coleoptile growth through the ABA pathway instead of the ethylene and GA pathway, by targeting the promoters of OsNCED3, OsZEP1, and OsABA8ox1. We also found that OsNAC2 regulates downstream targets in a time-dependent manner by binding to the promoter of OsKO2 in the seedling period but not in the germination stage. Our finding enriched the regulatory network of ethylene, ABA, and GA in the germination of rice seeds and seedling growth, and uncovered new insights into the difference of transcription factors in targeting their downstream components.